Optimasi Penjadwalan Perawat Dan Bidan Dengan Pendekatan Metode Algoritma Genetika Pada Puskesmas Kecamatan Purwosari - Chandra, Alfian Bima; Farahdiansari, Ardana Putri; Stighfarrinata, Rizky (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Purwosari Community Health Center provides structured healthcare services with two types of services, inpatient and outpatient care. Although inpatient services run smoothly, nurse shift scheduling still relies on Microsoft Excel and often encounters schedule conflicts. To address this issue, the use of genetic algorithm method is proposed. Genetic algorithm offers multi-criteria and multi-objective solutions for scheduling, integrating concepts from genetics and scientific biological processes. Thus, the "schedule collision" problem can be effectively addressed, enhancing the efficiency of nurse shift scheduling in Purwosari Community Health Center's inpatient care.